“Corneal Nerves, CD11c+ Dendritic Cells and Their Impact on Ocular Immune Privilege” - Niederkorn, Jerry Y. (Frontiers in Immunology, 2021)
The eye and the brain have limited capacities for regeneration and as such, immune-mediated inflammation can produce devastating consequences in the form of neurodegenerative diseases of the central nervous system or blindness as a result of ocular inflammatory diseases such as uveitis. Accordingly, both the eye and the brain are designed to limit immune responses and inflammation – a condition known as “immune privilege”. Immune privilege is sustained by physiological, anatomical, and regulatory processes that conspire to restrict both adaptive and innate immune responses.